2015
DOI: 10.1016/j.jphs.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of glaucocalyxin B in microglia cells

Abstract: Over-activated microglia is involved in various kinds of neurodegenerative process including Parkinson, Alzheimer and HIV dementia. Suppression of microglial over activation has emerged as a novel strategy for treatment of neuroinflammation-based neurodegeneration. In the current study, anti-inflammatory and neuroprotective effects of the ent-kauranoid diterpenoids, which were isolated from the aerial parts of Rabdosia japonica (Burm. f.) var. glaucocalyx (Maxim.) Hara, were investigated in cultured microglia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…[10][11][12] Glaucocalyxin is an ent-kaurane diterpenoid isolated from R. japonica. 15 However, the effect of GLB on oxygen-glucose-deprivation/reperfusion (OGD/R)-induced cell injury in PC-12 cells has not been explored. Pan et al 14 reported that GLB inhibited the proliferation of human cervical cancer cells in vitro through the induction of apoptosis and autophagy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Glaucocalyxin is an ent-kaurane diterpenoid isolated from R. japonica. 15 However, the effect of GLB on oxygen-glucose-deprivation/reperfusion (OGD/R)-induced cell injury in PC-12 cells has not been explored. Pan et al 14 reported that GLB inhibited the proliferation of human cervical cancer cells in vitro through the induction of apoptosis and autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, one study reported that GLB significantly suppressed the production of nitric oxide, tumor necrosis factor, interleukin, and expression of cyclooxygenase and inducible nitric oxide synthase in the lipopolysaccharide (LPS)-activated microglia cells. 15 However, the effect of GLB on oxygen-glucose-deprivation/reperfusion (OGD/R)-induced cell injury in PC-12 cells has not been explored. Our results indicated that GLB protects against OGD/R-induced neuronal injury in PC-12 cells by activating the Akt/mTOR signaling pathway.…”
mentioning
confidence: 99%
“…Glaucocalyxin B (GLB) is an ent -kauranoid diterpenoid isolated from a perennial herb, Rabdosia japonica . GLB has been reported to suppress lipopolysaccharide (LPS)-induced inflammation in microglia [11]. GLB inhibits the proliferation of human cervical cancer cells through inducing apoptosis and autophagy, which is mediated by the PI3K/Akt signaling pathway [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the gut, iNOS induces intestinal barrier damage [31], and in the brain causes nitrosylation of proteins and cell death with neurological consequences like dementia, Alzheimer or Parkinson diseases [32,33]. Even though NO is locally produced, its effects can diffuse systemically, thus influencing the progression of the disease [34][35][36] [ [34][35][36]. Bioactive nutrients possibly modulate individual microbiome responses limiting inflammation and free radical synthesis, including NO [37].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, in our first experiment, we identified and decided to focus on the term "nitric oxide synthase" [27] as a promising novel bridging term. From the set of articles that were used as input to CrossBee the expert carefully reviewed the four articles containing this term; three from the "Alzheimer" domain [34][35][36] [ [34][35][36] and one from the "gut microbiota" domain [30]. In addition, the combined query "Alzheimer gut nitric oxide" in PubMed revealed that there are no articles that correspond to this query, which is especially interesting, indicating that this connection was not previously explored in the available literature.…”
Section: Discussionmentioning
confidence: 99%